Collaborative strategies between fashion and gaming industry (ModaPalavra e-periódico, 2024)
In the digital environment, most individuals of all ages consider gaming as their favorite form of entertainment. This scenario has led to the fashion industry’s interest in making approaches with gaming platforms. In this perspective, this study aims to highlight the collaborative strategies between the fashion and gaming industries in digital fashion consumption. The methodology used is characterized as of applied nature, in which the study objective was descriptive through a case study with a qualitative approach. The collaborative strategy analyzed was between the companies Riot Games and Louis Vuitton, and the data collection instruments used interviews and documentary research. In the end, it is concluded that collaborative strategies between the fashion and gaming industries in digital fashion consumption can benefit both companies involved.
Keywords: collaborative strategies; digital fashion; games